Theorising narratives of exile and belonging : the importance of Biography and Ethno-mimesis in “understanding” asylum - O’Neill, Maggie; Harindranath, Ramaswami (Qualitative Sociology Review, 2006)
The article explores the use and importance of taking a biographical approach to conducting participatory action research (PAR) with asylum seekers and refugees in order to: better understand lived experiences of exile and belonging; contribute to the important field of Biographical Sociology; provide a safe space for stories to be told; and in turn for these stories to feed in to policy and praxis. The authors’ combined work on the asylum-migration nexus, the politics of representation and participatory action research methodology (PAR) as ethno-mimesisi argues for the use of biography to contribute to cultural politics at the level of theory, experience and praxis, and is constitutive of critical theory in praxis. PAR research undertaken with Bosnian refugees in the East Midlands and Afghan refugees in London will be the focus around which our analysis develops. We develop a case for theory building based upon lived experience using biographical materials, both narrative and visual, as critical theory in practice towards a vision of social justice that challenges the dominant knowledge/power axis embedded in current governance and media policy relating to forced migration. The dominant power/knowledge axis related to forced migration is embedded in current (New Labour) governance and re-presented in some media texts as identified below. New Labour governance is symbolised in the competing discourses of a) strong centralised control and b) more open systems, network and partnership based governance (Newman, 2003: 17-23; Clarke, 2004; Lewis, 2000). Open systems are made up of partnerships and networks – “joined up government”, “that transcends the vertical, departmental structures of government itself” (Newman, 2003: 20). to develop or foster a consensual style of governing. Progressive governance is defined by Newman (2003:15) as involving a significant shift from governance through hierarchy and competition to governance through networks and partnerships with an emphasis upon inclusion. Progressive governance involves the production of techniques and strategies of responsibilisation of citizens operationalised through the development of networks, alliances, and partnerships, with a strong focus upon active citizenship. Thus, spreading responsibility for social control to non state agencies and “communities” (Garland, 2001). In relation to forced migration/asylum discourses around the exclusion of the “other” (involving criminalisation, detention and deportation) and the maintenance and control of borders (developing ever more tighter controls on entry and asylum applications) exist in tension with discourses that speak of human rights, responsibilities and possibilities for multi-cultural citizenship especially in the community cohesion literature. There is a conflict at the heart of New Labour’s approach to asylum policy linked to the “alterity” of the asylum seeker that promulgates hegemonic ideologies and discourses around rights to belonging and citizenship, perceived access to resources (redistribution) and misrecognition fostering suspicion of the “stranger”. Alongside discourses of fairness and rights to enter and seek refuge, there exist regressive discourses that water down the vitally important actual and symbolic 1951 UN convention, and foster a split between “bogus” and “genuine” refugees, making it extremely hard to seek asylum in the UK.